Cruise Control of an Electric Vehicle Propolled by a BLDC Motor - Hasni Anwar; Lassioui Abdellah; El Fadil Hassan; El Asri Yassine; El Ancary Marouane; Bentalhik Issam; El Jeilani Sidina; Nady Soukaina (EPJ Web of Conferences)
Currently, green technology is a global priority, with electricity being a key clean energy source driving its adoption. electric motors serve as vital components for various applications, converting electrical power into mechanical energy and vice-versa. Electric drives such as Brushless DC motors (BLDC) have attracted considerable interest due to their minimal maintenance requirements and compact construction, offering promising alternatives for improving the lifespan of Electric Vehicles (EV). Achieving optimal performance of an EV, propelled by a BLDC motors necessitates effective speed and torque control techniques, also known as cruise control. In this paper, the operating principle of a BLDC drive is first discussed. Secondly, the dynamic modelling task has been performed. Thirdly, a cruise controller has been designed to maintain the speed of the EV at the desired reference. The performance of the control technique has been tested using MATLAB/Simulink software. The results achieved prove the effectiveness of the control technique used in various test scenarios.